Desempenho de lithothamnium sp. no cultivo de manga ‘Palmer’ em argissolo. - Freitas, Maria Auxiliadora Conceição de (2016)
Mang crop in the San Francisco Valley region is a growing activity and with significant participation in the Brazilian fruit market. Thus, it has sought the improvement of production techniques, as the introduction of alternative sources of nutrients to increase their productivity, and ensure the quality of the fruits. Therefore, the objective of the work was to evaluate the effect of complex calcareous algae, in formulating Lithothame, in the soil fertility, nutritional status, yield, and fruit quality of mango 'Palmer'. The experiment was conducted from August/2014 to June/2015 in a commercial orchard of mango 'Palmer' belonging to the Special Fruit Farm in Petrolina county, Pernambuco State, Brazil. The experiment design was the one of completely randomized blocks with three replications, and arrangement of split split-plots, being the plots concerning to doses applied to the soil (0; 5; 20; 60, and 100 kg ha-1 ), the subplots concerning two particle sizes of Lithothame (600, and 1200 mesh), and the subsubplots referring to calcium nitrate concentrations applied to the leaves (2.5% calcium nitrate, 0.5, 1.5, and 3% of NO3- - Lith). The response of mango tree to treatment was evaluated by the analysis of foliar and fruit content of N, P, K, Ca, Mg, and of the N/Ca, and K/Ca in leaf tissues and fruits (skin, and pulp); yield (NMF plant-1 , MMF and total productivity), and post-harvest fruit quality (%PM, firmness, SS, ATT, SS/ATT and pH). Nutrient contents in the leaves were determined before flowering, early blooming, full blooming, and in the fruit ripening stage. Calcareous algae treatments did not alter soil fertility. However, the leaf content of P, K, and Ca increased with the applications of Lithothame, being more accentuated in the grain size of 1200 mesh. The highest Ca contents in the skin (1.84 g kg-1 ), and pulp (0.56 g kg-1 ) were obtained in a particle size of 1200 mesh when applied 41.83, and 34.14 kg ha-1 Lithothame, respectively. These results show a favorable effect of calcareous algae in mango crop, observing that the high dosage treatments of Lithothame did not present any nutrient content. The application of Lith nitrate influenced the 'Palmer' mango production, being the highest productivity achieved in the treatment with 0.5% of Lith nitrate. Regarding the post-harvest fruit quality, there was no difference between treatment with 0.5% Lith nitrate, and 2.5% calcium nitrate for the SS content. Thus, the 0.5% Lith nitrate kept the mango fruits with the same flavor.